Partial Least Square Structural Equation Model “PLS-SEM” to Predict Total Quality Management in UAE Higher Education: A Comprehensive Framework for Organizational Performance Enhancement - GUPTA Babeet; SRIVASTAVA Riktesh; UC Harish; ABURAYYA Ahmed (Foundations of Management)
The effectiveness of organizations and the satisfaction of customers are both significantly improved by providing outstanding quality. To better meet the needs of their consumers, an increasing number of firms are implementing quality improvement programs such as total quality management (TQM). The major objective of this research paper is to examine the effects of TQM components on the efficiency and effectiveness of UAE higher education institutions (HEIs). The association between TQM components and organization performance was investigated using a quantitative research technique based on a survey study design. The partial least square structural equation model (PLS-SEM) was used to quantify the reflectiveness of 99 data. The study found that TQM has a positive impact on employee satisfaction and service quality in HEIs. It was revealed that TQM has a significant impact on organizational performance, with service quality serving as a mediator. Furthermore, the results revealed that service quality and students’ satisfaction are fully mediating the relationship between TQM and organizational performance. The current study concludes that HEIs are implementing TQM to enhance market performance and comprehend the evolving business trends. The study has added to the body of information about the relationship between TQM elements and organization performance.